Impact of Organization Culture and Organizational Commitment to Lecturer Performance in Riau Province Islands with Job Satisfaction as Intervening Variable - S.L. Ratnasari; G. Sutjahjo; Adam (Nusantara Science and Technology Proceedings)
The purpose of this study is to determine the impact of organizational culture and organizational commitment to lecturer performance, through job satisfaction as an intervening variable. The method in this study using analysis descriptive approach, this kind of research is quantitative and descriptive, nature of this study was descriptive explanatory. Population in this research were all certified lecturer in Riau Province islands are 154 lecturers. As for the number of samples in this study are 154 lecturers in Riau Province islands using census. Data were collected with a list of questions in questioner and study documentation. For data calculation analysis, this study using path analysis, processing the data using computers program SPSS. This research resulted in conformity and acceptance of the hypothesis. The impact of Organizational Culture to Job Satisfaction; The impact of Organizational Commitment to Job Satisfaction; The impact of Organizational Culture to Job Performance; The impact of Organizational Commitment to Lecturer Performance; The impact of Job Satisfaction to Lecturer Performance, The impact of Organizational culture to Lecturer Performance through Job Satisfaction, The impact of Organizational Commitment to Lecturer Performance through Job Satisfaction. The result of this research was there is a significant and positive impact, directly all of the dependent variables to the independent variable. This research founded the indirect impact of Organizational Commitment to Lecturer Performance through Job Satisfaction, but for the effect of Organizational Culture to Lecturer Performance through Job Satisfaction, the data analyses give the direct impact of the variable Organizational culture to job satisfaction is bigger than the impact of the Organizational Culture has impact to Lecturer Performance through Job Satisfaction